Lokakarya Komunitas Belajar Sekolah Penggerak di Kabupaten Tegal - Meilina Haris Mayekti; Dinar Faiza; Ade Christanty Yudha Bestari (Migunani Nusantara: Jurnal Pengabdian Kepada Masyarakat, 2024)
In Supporting of the Implementation of the Merdeka Curriculum, the PSP Learning Community Workshop Cohort 2. The PSP Learning Community Workshop Cohort 2 was held on September 7, 2024, in each Regency/City in Central Java Province. This activity is part of ongoing efforts to strengthen the capacity of school principals, school supervisors, and teachers in guiding and supporting educational transformation within educational institutions. The objectives of the PSP Learning Community Workshop Cohort 2 are as follows: (1) Understanding the Inquiry Cycle: Participants are expected to understand the inquiry cycle, including initial reflection, planning, implementation, and evaluation within the learning community; (2) Adaptive Self-Development Plans: Participants will develop adaptive plans for self-improvement, focusing on student-centered leadership in educational institutions. (3) Mentoring Design: Participants will create mentoring designs to optimize learning communities in schools. The workshop involves school principals, two Learning Committee teachers, and school supervisors from educational institutions implementing the third year of PSP Cohort 2. The event is conducted face-to-face (offline), allowing direct discussion and collaboration among participants to strengthen their understanding and implementation of the Merdeka Curriculum.